A community engaged primary healthcare strategy to address rural school student inequities: a descriptive paper. (20th March 2019) - Jones, Debra; Ballard, Jacqueline; Dyson, Robert; Macbeth, Peter; Lyle, David; Sunny, Palatty; Thomas, Anu; Sharma, Indira
Abstract: Aim: This descriptive paper aims to describe the design and implementation of a community engaged primary healthcare strategy in rural Australia, the Primary Healthcare Registered Nurse: Schools-Based strategy. This strategy seeks to address the health, education and social inequities confronting children and adolescents through community engaged service provision and nursing practice. Background: There have been increasing calls for primary healthcare approaches to address rural health inequities, including contextualised healthcare, enhanced healthcare access, community engagement in needs and solutions identification and local-level collaborations. However, rural healthcare can be poorly aligned to community contexts and needs and be firmly entrenched in health systems, marginalising community participation. Methods: This strategy has been designed to enhance nursing service and practice responsiveness to the rural context, primary healthcare principles, and community experiences and expectations of healthcare. The strategy is underpinned by a cross-sector collaboration between a local health district, school education and a university department of rural health. A research framework is being developed to explore strategy impacts for service recipients, cross-sector systems, and the establishment and maintenance of a primary healthcare nursing workforce. Findings: Although in the early stages of implementation, key learnings have been acquired and strategic, relationship, resource and workforce gains achieved.